2014
DOI: 10.1108/ijlss-04-2012-0002
|View full text |Cite
|
Sign up to set email alerts
|

Lean manufacturing implementation using value stream mapping as a tool

Abstract: Purpose – Value stream mapping (VSM) is a lean manufacturing (LM) tool used for analyzing material and information flow on a specific product family. The purpose of this article is to address the importance of VSM in LM environment in an Indian auto components industry. Design/methodology/approach – The case study approach has been used to show the applicability and importance of VSM in an Indian auto components company, in which the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 47 publications
0
16
0
6
Order By: Relevance
“…A busca do layout mais eficiente também ocorre no Lean Manufacturing, devido a busca de reduzir tempos não produtivos, como os tempos de movimentação das peças na linha de produção. (Carmignani, & Zammori, 2015 p. 994;Lopes, Freitas, & Sousa, 2015;Jasti, & Sharma, 2014). O mapeamento do fluxo de valor para reduzir atividades não produtivas é um dos destaques da produção Lean Manufacturing; a. Melhoria da qualidade (Chaplin, & O'rourke, 2016).…”
Section: Elementos Metodologias E Etapas Da Aplicação Do Lean Manufacturingunclassified
See 2 more Smart Citations
“…A busca do layout mais eficiente também ocorre no Lean Manufacturing, devido a busca de reduzir tempos não produtivos, como os tempos de movimentação das peças na linha de produção. (Carmignani, & Zammori, 2015 p. 994;Lopes, Freitas, & Sousa, 2015;Jasti, & Sharma, 2014). O mapeamento do fluxo de valor para reduzir atividades não produtivas é um dos destaques da produção Lean Manufacturing; a. Melhoria da qualidade (Chaplin, & O'rourke, 2016).…”
Section: Elementos Metodologias E Etapas Da Aplicação Do Lean Manufacturingunclassified
“…Análise do Fluxo de valor (Carmignani, & Zammori, 2015 p. 994); SMED (Lopes et al, 2015). O mapeamento de valor (Jasti, & Sharma, 2014).…”
Section: Nívelunclassified
See 1 more Smart Citation
“…Aditya Sharma [4] checked the application of VSM in Indian auto component Industry and proved it to be much beneficial since it helped to identify all types of lean waste and improvement areas where other tools for improvements. Also it was found that top management involvement is one of the important factors for successful lean implementation.…”
Section: A Lean In Automotive Industrymentioning
confidence: 99%
“…Singh, Garg, & Sharma, 2009) and automotive manufacturing (Lacerda, Xambre, & Alvelos, 2016;H. Singh & Singh, 2013;Vamsi Krishna Jasti & Sharma, 2014). Others have focused on less common areas such as product development (Peek & Chen, 2011;Tyagi, Choudhary, Cai, & Yang, 2015), architecture (Lima, Rolim, & Alves, Thais da C L, 2010), construction (Matt, Krause, & Rauch, 2013), call centre (Piercy & Rich, 2009), transport (Villareal, Garza, Rosas, & Garcia, 2012) and maintenance service (Kasava, Yusof, Khademi, & Saman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%